2018
DOI: 10.1002/ep.12837
|View full text |Cite
|
Sign up to set email alerts
|

Development of a national water‐energy system model with emphasis on the power sector for south africa

Abstract: A comprehensive archive of information and data pertaining to the development process is available via the Energy Research Data Portal for South Africa. The portal hosts technical reports and data fully describing the model development, estimation of costs and technical parameters; and that of stakeholder engagement for model validation and scenario critique. http://energydata.uct.ac.za/organization/erc-water-energy-nexus © 2018 American Institute of Chemical Engineers Environ Prog, 37: 132–147, 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…A more comprehensive illustration of existing nexus research is shown in Figure 6, in which black lines represent a focus on the study of a particular resource (e.g., food, energy, or water), yellow lines indicate the study of integrated systems with two principal resources, and gray dashed lines emphasize the interlinkages of subsections of different nexuses. In terms of focus and level of integration, 29 papers focused on the FEW nexus, but these mostly aimed to conduct general analysis and systematic review, whereas 10 papers focused on water (Larsen & Drews, 2019;Rosa & D'Odorico, 2019), 5 on food (Abdelkader et al, 2018;Neto et al, 2018;Zhang, Campana et al, 2018), 4 on energy (Yuan et al, 2018;Ahjum et al, 2018;Whitney et al, 2019), 9 on water-energy nexus (Engstr€ om et al, 2017;Wang et al, 2017;Liu et al, 2019), 2 on energyfood (Hanes et al, 2018), and 1 on water-food (Zhang & Vesselinov, 2017). The rest of the articles applied nexus research from various angles.…”
Section: Featured Analysis Of the Few Nexus Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A more comprehensive illustration of existing nexus research is shown in Figure 6, in which black lines represent a focus on the study of a particular resource (e.g., food, energy, or water), yellow lines indicate the study of integrated systems with two principal resources, and gray dashed lines emphasize the interlinkages of subsections of different nexuses. In terms of focus and level of integration, 29 papers focused on the FEW nexus, but these mostly aimed to conduct general analysis and systematic review, whereas 10 papers focused on water (Larsen & Drews, 2019;Rosa & D'Odorico, 2019), 5 on food (Abdelkader et al, 2018;Neto et al, 2018;Zhang, Campana et al, 2018), 4 on energy (Yuan et al, 2018;Ahjum et al, 2018;Whitney et al, 2019), 9 on water-energy nexus (Engstr€ om et al, 2017;Wang et al, 2017;Liu et al, 2019), 2 on energyfood (Hanes et al, 2018), and 1 on water-food (Zhang & Vesselinov, 2017). The rest of the articles applied nexus research from various angles.…”
Section: Featured Analysis Of the Few Nexus Literaturementioning
confidence: 99%
“…In addition, Kumazawa et al (2017) proposed a knowledge sharing and collaboration tool for interdisciplinary research based on an ontology engineering approach, which is a type of semantic web technology that offers common terms, concepts, and semantics. Ahjum et al (2018) conducted a case study of a water-for-energy development nexus based on the South African national energy-economic system model. The model is a non-spatial national representation of energy goods, service flows, and energy technologies with associated costs and emissions.…”
Section: Tools and Techniquesmentioning
confidence: 99%
“…A fossil future in Zimbabwe would involve the continued expansion of its coal-fired power plants. In the same way as its water scarce neighbor in the South, dry cooling technology might be employed to ensure its resilience to low water availability [43]. While unlikely, a future based on coal provides this analysis (as it has done others) with a convenient backdrop against which lower carbon futures might be evaluated [44].…”
Section: A Fossil Futurementioning
confidence: 99%
“…A Fossil Future A fossil future in Zimbabwe would involve the continued expansion of its coal-fired power plants. Like its water scarce neighbor in the South, dry cooling technology might be employed to ensure it resilience to low water availability (Ahjum 2018). While unlikely, a future based on coal provides this analysis (as it has done others) with a convenient backdrop against which lower carbon futures might be evaluated (Sims et al 2003).…”
Section: Electricity Futures In Zimbabwementioning
confidence: 99%